Restorative justice for survivors of sexual abuse - Marinari, Angela (Policy Press shorts. Research., 2021)
Drawing on interviews with survivors, this book gives a voice to survivors and illuminates how restorative justice processes can meet their justice needs. With a unique focus on the people around the survivor rather than on the abuser, it offers radical solutions for the development of restorative justice programs and policy initiatives.